Upaya Penanaman Kebiasaan Olah Raga Pada Mahasiswa PGSD Melalui Proyek Hidup Sehat - Widiastuti Widiastuti (Peneliti.net, 2022)
This research is motivated by the low exercise habits among PGSD students. This low exercise habit makes the condition of PGSD students physically often feel tired, body stiff and achy. While psychologically, PGSD students often experience excessive stress, anxiety, and worry. From the spiritual side, PGSD students also felt less enthusiastic or enthusiastic in participating in spiritual activities. Therefore, an effort is needed to overcome these problems, namely by implementing a healthy living project. The purpose of this study was to describe efforts to inculcate exercise habits in PGSD students through a healthy living project. The method used in this research is descriptive qualitative. The subjects of this study were fourth semester PGSD students. Data were collected using observation, interviews, and documentations. The results of this study indicate that the implementation of a healthy living project carried out for approximately two months by exercising three times a week can in still exercise habits in PGSD students. Students who had never previously done sports became happy and interested in doing sport regularly. In addition, the students also felt changes in their physical, psychological, and spiritual conditions after completing the healthy living project in the from of sport. This is the motivation that encourages PGSD students to continue the project of heathy living as a daily lifestyle. Thus, it can be concluded that efforts to in still exercise habits in PGSD students